Ecotoxicological assessment of soil contaminated by military operations using earthworms Eisenia fetida - Khyzhnyak, S. V.; Korniyenko, V. I.; Samkova, O. P.; Midyk, S. V.; Iakubchak, O. M. (Regulatory Mechanisms in Biosystems, 2026)
A reas of s oil cover of agricultural lands in Mykolaiv region , d egraded due to military operations and characterized by complex pollution, were examined for ecotoxicity. Soil biotesting, according to ISO standards, was conducted under laboratory conditions (14-day exposure) using earthworms Eisenia fetida . High toxicity of the experimental (degraded) soil with respect to E . fetida (100% mortality of organisms) was established. However, with a twofold reduction in the proportion of contaminated soil in the earthworms’ habitat, this index wa s reduced by approximately half. It is shown that possible effects of soil contamination, which disrupt the vital functions of earthworms, are accompanied by a redistribution of fatty acids (FAs) content of their total lipids. FAs analysis was performed on a Trace GC Ultra gas chromatograph with a Flame Ionization Detector, which a l lowed the identification of 19 fatty acids in the worms’ body. A decrease in the content of unsaturated FAs by 24.3%, in particular monounsaturated FAs, mainly due to oleic acid (C18:1ω9), was revealed as a result of the impact of soil contamination on eart h worms. In addition, an increase in the content of saturated FAs by 55.7%, especially such important FAs as palmitic acid (C16:0) by 53.7% and stearic acid (C18:0) by 50.1%, was detected, which may lead to structural and functional changes in cell me m branes. An important fact is the decrease in the content of polyene FAs of the ω6 family, in particular arachidonic acid (C20:4ω6) by 39.2% and the ω3 family, which are involved in the regulation of a wide range of physiological processes. The reorganization of the profile of lipid FAs of E . fetida can be considered as an early marker of metabolic changes in the earthworm body. The obtained results contribute to the objective assessment of the ecotoxicological consequences of soil damage as a result of military operations and contribute to an effective strat e gy for managing contaminated areas of agricultural land.